INNOVATIVE TECHNOLOGIES IN THE PRODUCTION OF SEWING PRODUCTS: PREPARATION DEPARTMENT EQUIPMENT - РУБАНКА, М. М.; КОВАЛЬОВ, Ю. А.; РУБАНКА, А. І. (Technologies and Engineering, 2023)
Purpose. Systematic search for rational and effective solutions for the technological process of the preparation department of a sewing enterprise, including through the introduction of modern innovative equipment. Methodology. The method of systematic, theoretical and comparative analyzes was used in the work. Theoretical studies are based on the basic provisions of light industry production technology. Findings. It was established that the expansion of the range of sewing products, the rapid introduction of the latest materials and processing methods leads to the need for partial or complete modernization of sewing enterprises, including the preparatory department of a sewing enterprise, due to the introduction of both improved methods of organizing the production process and the introduction of the latest innovative equipment. The classification of the standard equipment of the preparation department of a sewing enterprise is proposed, which allows conditionally classifying the equipment of the preparation department into equipment for supplying materials to the department from the materials warehouse, equipment for transport and logistics systems in a warehouse with single- and multi-level racks, equipment for moving materials between sections of the department, and equipment for measuring and rejecting materials; the main requirements for the equipment used in the technological process of preparation department of a sewing enterprise have been determined; the ways of possible improvement of the preparation department of a sewing enterprise have been outlined. Originality. A systematic analysis of the equipment used in the preparatory workshops of sewing enterprises was carried out. The classification of the standard equipment of the preparation department of a sewing enterprise is proposed. Prospective directions of development thanks to the use of innovative technologies, in particular automation and robotics, are indicated. It has been established that the introduction of modern innovative equipment significantly increases the efficiency of the preparatory department. Practical value. The obtained results of the study can be used in the design, partial renewal and complete modernization of the preparatory department of sewing enterprises, which will lead to an increase in labor productivity.